A Pediatric Case of Chandipura Virus Encephalitis: Clinical Presentation and Management during an Outbreak - Devesh N Joshi; Urvi Dantaliya; Shrushti Gandhi; Vishalkumar Patel; Nitiben S Gor; Geet Gunjana (Pediatric Infectious Disease)
Introduction: Chandipura virus (CHPV) is an emerging but underrecognized cause of acute encephalitis syndrome (AES), primarily affecting children in the Indian subcontinent. Typically, CHPV presents as a severe disease with high mortality, with nearly two-thirds of cases resulting in death. Case description: This report highlights an atypical presentation of CHPV encephalitis in an 18-month-old male during a recent outbreak. The child presented with symptoms including high-grade fever, generalized pustular rash, abnormal behavior, and a single episode of generalized tonic-clonic seizures (GTCS). This case is particularly significant due to its mild course and the involvement of skin manifestations, which are uncommon in CHPV infections. Initial investigations revealed normal organ function and normal cerebrospinal fluid (CSF) analysis. The diagnosis was confirmed by positive CHPV serology in serum samples. The patient responded well to supportive care and was discharged after 12 days without further complications. Discussion and conclusion: During the outbreak, six additional cases of suspected CHPV encephalitis were managed, with outcomes ranging from full recovery to fatal multiorgan failure, underscoring the virus’s typical severity. The unique presentation of this case contrasts with the usually fatal course of CHPV, emphasizing the variability in clinical manifestations and the importance of early diagnosis and management. This case highlights the need for awareness of CHPV, especially in regions where it is endemic, and calls for further research into the virus’s pathogenesis and clinical spectrum.